The estimation of reservation wages: A simulation-based comparison - Julian Sebastian Leppin (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
This paper examines the predictive power of different estimation approaches for reservation wages. It applies stochastic frontier models for employed workers and the approach from Kiefer and Neumann (1979b) for unemployed workers. Furthermore, the question of whether or not reservation wages decrease over the unemployment period is addressed. This is done by a pseudo-panel with known reservation wages which uses data from the German Socio-Economic Panel as a basis. The comparison of the estimators is carried out by a Monte Carlo simulation. The best results are achieved by the cross-sectional stochastic frontier model. The Kiefer-Neumann approach failed to predict the decreasing reservation wages correctly.
Keywords: C21; C23; J64; 330; job search theory; Monte Carlo simulation; reservation wages; stochastic wage frontiers